2015
DOI: 10.1152/japplphysiol.00420.2015
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory activation of abdominal muscle is associated with improved respiratory stability and an increase in minute ventilation in REM epochs of adult rats

Abstract: Breathing is more vulnerable to apneas and irregular breathing patterns during rapid eye movement (REM) sleep in both humans and rodents. We previously reported that robust and recurrent recruitment of expiratory abdominal (ABD) muscle activity is present in rats during REM epochs despite ongoing REM-induced muscle atonia in skeletal musculature. To develop a further understanding of the characteristics of ABD recruitment during REM epochs and their relationship with breathing patterns and irregularities, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 34 publications
8
32
1
Order By: Relevance
“…The observation (i) that active expiration failed to be consistently recruited by hypercapnia in both sleeping and awake rats is consistent with the observation that active expiration was not consistently recruited in REM sleep (Andrews & Pagliardini, ). It seems that factors other than levels of chemical drive and state influence abdominal expiratory activity.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The observation (i) that active expiration failed to be consistently recruited by hypercapnia in both sleeping and awake rats is consistent with the observation that active expiration was not consistently recruited in REM sleep (Andrews & Pagliardini, ). It seems that factors other than levels of chemical drive and state influence abdominal expiratory activity.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, other reports in the literature showed that active expiration is recruited during sleep in rats and humans (Pagliardini et al . ; Andrews & Pagliardini, ; and in our present study). The fact that RTN neurons drive active expiration only during wakefulness suggests that different mechanisms to recruit active expiration may be involved during sleep.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies, also performed in rats, suggest that active expiration, i.e. expiratory recruitment of abdominal muscles, occurs during both NREM and REM sleep (Andrews & Pagliardini, ; Sherrey, Pollard, & Megirian, ), although it is more frequent after apnoea and high respiratory variability events observed in REM sleep (Andrews & Pagliardini, ).…”
Section: Introductionmentioning
confidence: 93%